Lost in a Sea of Letters : Saʿd al-Dīn Ḥamūya and the Plurality of Sufi Knowledge - Uy II, Cyril V., (Islamicate Intellectual History ;, 2025)
In Lost in a Sea of Letters , Cyril Uy explores the life and work of Saʿd al-Dīn Ḥamūya (d. 1252), a Mongol-era Sufi whose arcane treatises inspired generations of mystics and messiahs. Reading Ḥamūya in dialogue with contemporaries across Central Asia, Iran, and the Eastern Mediterranean, Uy excavates a world in which knowledge was an embodied sensibility: a way of being that could improvise across all dimensions of human experience. Ḥamūya's performative writing reworked the foundations of this knowledge, provoking readers to live reality through the cacophony of his Sufi free jazz. Foregrounding Ḥamūya's deconstructive ethos and radical openness to interpretation, Uy reveals how embracing plurality could thrive as a mode of social, intellectual, and spiritual competition.